2010
DOI: 10.1038/ejcn.2010.267
|View full text |Cite|
|
Sign up to set email alerts
|

Association of maternal folate nutrition and serum C-reactive protein concentrations with gestational age at delivery

Abstract: Background/objectives: C-reactive protein (CRP) is the most extensively studied inflammatory risk marker, and elevated serum CRP concentrations in pregnant women are known to be associated with subsequent development of preeclampsia and preterm delivery. Researchers have suggested that folate intake may help to control the inflammation process. We examined whether folate nutrition modifies the relationship between serum CRP concentration and gestational age at delivery. Subjects/methods: Serum CRP concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…General information on demographic factors, socioeconomic factors and healthrelated behaviors (including the use of dietary supplements) was gathered directly from the pregnant women. The method used to survey the general characteristics has been described in detail elsewhere (Kim et al, 2011).…”
Section: Study Subjects and Data Collectionmentioning
confidence: 99%
“…General information on demographic factors, socioeconomic factors and healthrelated behaviors (including the use of dietary supplements) was gathered directly from the pregnant women. The method used to survey the general characteristics has been described in detail elsewhere (Kim et al, 2011).…”
Section: Study Subjects and Data Collectionmentioning
confidence: 99%
“…There is growing interest in the issue of whether dietary factors can affect the risk of preterm delivery, and several nutritional factors have been investigated with both inconclusive and conflicting results, including the Mediterranean diet, fish consumption, vitamin and mineral supplements (eg, folic acid and vitamins C and E), caffeine, and probiotic food (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…CRP is modulated by nutritional status and deficiencies of vitamins A [22], D [23] and folic acid [24], but several studies have reported no association of CRP with vitamin B 12 [25, 26]. CRP reportedly is higher in obese pregnant women [27], but this association was lost by the end of pregnancy [28].…”
Section: Introductionmentioning
confidence: 99%